Analysis of judicial practice in cases of bullying at the institutions of professional (vocational) education - O. H. Yushkevych (Law and Safety)
The article is devoted to the monitoring of court decisions rendered by courts in the period from 2019 to 2021. in cases of administrative offenses, the subject of which is the bullying of participants in the educational process at the institutions of professional (vocational) education. It is determined that the subjects of professional (vocational) education include applicants for professional (vocational) education and teachers who are potential parties to bullying: the offender (buller), the victim (victim of bullying), observers. It is noted that bullying is a consequence of violation by subjects of professional (vocational) education of the rights of other subjects of professional (vocational) education and their responsibilities under general and specialized regulations. It is established that the objective side of most cases is the actions of applicants for professional (vocational) education, which led to psychological and physical violence. It is noted that in bringing juvenile applicants for professional (vocational) education to administrative responsibility on a general basis in most cases, the court imposed an administrative penalty in the form of community service. Emphasis is placed on the fact that the court obliges applicants for professional (vocational) education to pay the court fee, but, given the property status of the minor, the court may release the latter from paying the court fee.